Isolation and antibiotic susceptibility screening of Pseudomonas Sp. from soil - Karim Hameed, Ashty (2014)
Pseudomonas is an aerobic Gram-negative, rod-shape bacterium which emerged as one of the most problematic nosocomial pathogens. To characterize Pseudpmonas species strains that are widespread in animal, plant, human, and environment especially soil and water, the soil sample was collected from T02 Building in Universiti Teknologi Malaysia. An isolated bacterium was cultured on nutrient agar and MacConkey agar plates. The results showed that using (MacConkey agar) at 37°C had highest recovery in the isolation of Pseudomonas. The colony produced white- pink pigment. Based on the Gram-staining method, Pseudomonas species was Gram negative with rod in shape, in pink color. The effects of temperature and incubation time, as well as their growth profiles in nutrient broth media, were studied. Pseudomonas can grow well in 37OC, which recorded maximum growth rate, and at 30OC Pseudomonas grow nearly similar to its growth rate at 37OC, while at 25OC growth of Pseudomonas was slow. Methods for isolation and characterization of Pseudomonas species based upon culture methods coupled with biochemical tests were used in this study. According to biochemical tests, Pseudomonas was catalase positive, citrate positive, gelatin liquefaction and oxidase positive whereas was negative for methyl red, urease, starch hydrolysis, triple sugar iron and Indole. However, to study the susceptibility of tested strain to different antibiotics using disk diffusion method the result showed that the isolated strain of Pseudomonas was resistance to Erythromycin, Gentamycin, Ampicillin and Penicillin, and susceptible to Ciprofloxacin, Imipenin, Lincomycin, Piperacillin and Tobramycin.